Cybercopters Swarm: Immersive analytics for alerts classification based on periodic data - Delcombel, Nicolas; Duval, Thierry; Pahl, Marc-Oliver (Frontiers in Virtual Reality, 2023)
This paper assesses the usefulness of an interactive and navigable 3D environment to help decision-making in cybersecurity. Malware programs frequently emit periodic signals in network logs. However, normal periodical network activities, such as software updates and data collection activities, mask them. Thus, if automatic systems use periodicity to successfully detect malware, they will also detect ordinary activities as suspicious ones and will raise false positives. Hence, there is a need to provide tools to sort the alerts raised by such software. Data visualizations can make it easier to categorize these alerts, as proven by previous research. However, traditional visualizations tools can struggle to display the large amount of data that needs to be treated in cybersecurity in a clear way. This is why this paper explores the use of Immersive Analytics to interact with complex datasets representations and to collect cues for alert classification. We created a prototype that uses a helical representation to underline periodicity in the distribution of one variable of a dataset. We tested this prototype in an alert triage scenario and compared it with a state of the art 2D visualization with regard to visualizations efficiency, usability, workload and flow induced.